UNJUK KERJA TANGKI TIMBUN T-127 TYPE CONE ROOF KAPASITAS 98.000 LITER DI PPSDM MIGAS CEPU: PERFORMANCE OF T-127 TYPE CONE ROOF STORAGE TANK WITH 98,000 LITER CAPACITY AT PPSDM MIGAS CEPU - Dhaifullah, Muhammad (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2025)
To keep this tank operating safely, it is necessary to evaluate the performance of this tank. Based on the results of the field work practice evaluation, the minimum thickness of the tank walls and roof was recorded at 0.0283 inches for the first course, 0.0226 inches for the second course, 0.0092 inches for the third course, and 0.09 inches for the roof. Actual thickness measurements showed 0.1693 inches (first course), 0.1614 inches (second course), 0.1417 inches (third course), and 0.1654 inches (roof). The measured corrosion rates varied, namely 0.03 mm/year (first course), 0.05 mm/year (second course), 0.06 mm/year (third course), 0.05 mm/year (first roof), and 0.08 mm/year (second roof). The estimated remaining life of the tank is 52.8 years for the first course, 46.8 years for the second course, 15.9 years for the third course, 42.28 years for the first roof, and 22.97 years for the second roof. Based on the analysis results, Tank T-127 is still feasible to operate with a maximum capacity of 97,998 m³.